INTRODUCTION TO TRANSLATION AND STRATEGIES - Mamasolieva Mohigul; Akhmedov Azimjon (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation. This article primarily focuses on interpreting the concept of "translation strategy." Currently, there lacks a precise definition of this term. Therefore, the main objective of this article is to examine the concept of "translation strategy" as a crucial component of strategic competence for aspiring translators. These are fundamental skills that students must acquire while developing their ability to employ translation strategies. The article also outlines the stages of translation and provides a classification of this concept.